The Determinant of Stock Price: Evidence on Food and Beverage Companies in Indonesia - Indo Yama Nasarudin; Suhendra Suhendra; Luthfia Farida Anggraini (ETIKONOMI, 2019)
One aspect that concerns investors in valuing stocks is financial performance. The purpose of this research is to examine the effect of financial performance, firm size, and corporate social responsibility disclosure to the stock price in food and beverage sector companies in Indonesia Stock Exchange. Using a purposive sampling method has done the sample collection method and eleven of eighteen companies, which listed in Indonesia Stock Exchange in the years of 20013-2017, are used as the research samples. The method used in this study was Structural Equation Modeling Partial Least Square (SEM-PLS). The result of the research shows that financial performance, firm size, and corporate social responsibility disclosure affect the stock price. This result implies that the firm should improve the internal factors to increase stock prices.JEL Classification: G23, G32